2016
DOI: 10.1186/s13578-016-0082-x
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of Aldo–keto reductase 1B10 is a novel independent prognostic indicator for nasopharyngeal carcinoma

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is one of the most common human head and neck cancers with high incidence in Southern China, Southeast Asia and North Africa. Because of its nonspecific symptoms, the early diagnosis of NPC is very difficult. The 5-year survival rate is not ideal in spite of great innovations in radiation and chemotherapy treatments. Highly sensitive and specific prognostic biomarkers are eager for NPC clinical diagnosis. To find specific target molecules is very important for individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The role of AKR1B10 in metastasis appears to be highly context dependent. In breast cancer, AKR1B10 has been reported to be significantly associated with metastasis [39] through upregulation of integrin α5 and δ-catenin [40] whereas, similar to our data, AKR1B10 overexpression in a nasopharyngeal carcinoma-derived cell line was found to result in a slower proliferation and a slower migration [41]. These differences may, at least partly, be explained by the different cell types Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The role of AKR1B10 in metastasis appears to be highly context dependent. In breast cancer, AKR1B10 has been reported to be significantly associated with metastasis [39] through upregulation of integrin α5 and δ-catenin [40] whereas, similar to our data, AKR1B10 overexpression in a nasopharyngeal carcinoma-derived cell line was found to result in a slower proliferation and a slower migration [41]. These differences may, at least partly, be explained by the different cell types Fig.…”
Section: Discussionsupporting
confidence: 83%
“…The prognostic significances of AKR1B1 and AKR1B10 individually have been reported for several different tumor types [15,41,[45][46][47]. In CRC we found that the expression of AKR1B1 was not altered in cancer cells compared to normal cells, both in silico and in in vitro experiments.…”
Section: Discussionsupporting
confidence: 60%
“…In NPC tissues, AKR1B10 expression seemed high specifically in SCC, but low in basal cell carcinoma, adenoid cystic carcinoma, adenocarcinoma, and undifferentiated carcinoma. However, Guo et al reported that AKR1B10 protein levels were reduced in most of the NPCs compared with paracarcinoma and benign tissues. The frequency of AKR1B10 positivity was significantly higher in patients with differentiated NPC than that in patients with undifferentiated NPC.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of AKR1B10 has been shown to be associated with poor prognosis among patients with breast, cervical, and liver cancers. By contrast, AKR1B10 expression has been reported as an independent variable of favorable prognosis in 3 studies of colorectal, gastric, and nasopharyngeal carcinomas . It is of interests to note that He et al found AKR1B10 expression levels are higher in nasopharyngeal carcinoma (NPC) tissues compared with the normal nasopharyngeal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation